2005
DOI: 10.1016/j.otohns.2005.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of regional metastases from cutaneous squamous cell carcinoma of the head and neck

Abstract: SCC of the skin of the head and neck with regional metastases has a high incidence of occult metastases in the parotid gland and the neck. Patients with metastases in both sites have a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
(29 reference statements)
1
17
1
1
Order By: Relevance
“…Furthermore, opinions differ as to the appropriate extent of neck dissection. [9][10][11][12] The current study represents a single institution analysis of prospectively collected data on the results of 295 neck dissections for cutaneous SCCHN. It was undertaken to determine the patterns of spread in the cervical lymph nodes, the relationship to the location of the primary tumor, and the morbidity associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, opinions differ as to the appropriate extent of neck dissection. [9][10][11][12] The current study represents a single institution analysis of prospectively collected data on the results of 295 neck dissections for cutaneous SCCHN. It was undertaken to determine the patterns of spread in the cervical lymph nodes, the relationship to the location of the primary tumor, and the morbidity associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study involving our institution previously recommended a supraomohyoid neck dissection in patients with anterolateral primaries and a comprehensive neck dissection for posterior primaries 9 while several other authors have recommended selective dissection of level I-II or I-III nodes in this setting regardless of the site of the primary tumor. [10][11][12] The most important outcome in this study revolves around the absence of level IV or V metastases in cPþN0 patients with pathologically negative nodes in levels II and III. Based on these findings, we support the use of elective level II/III dissection to stage the neck and determine the extent of adjuvant radiotherapy.…”
Section: Importance Of Level II and External Jugularmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Serving as the first echelon of metastases from the upper third of the face, including the scalp, cheek, and eyelid, it has been found that in general, skin cancer accounts for 50% of metastasis to the parotid gland. 46 These metastatic cells continue their descent and eventually seed to the ipsilateral cervical nodes. An obvious carcinoma seen on the face can make the diagnosis easier.…”
Section: Parotid Glandmentioning
confidence: 99%
“…(O'Hara, Ferlito et al 2010) Cervical neck node disease without parotid involvement can be seen in 18 to 41% of patients. (Andruchow, Veness et al 2006;Vauterin, Veness et al 2006) In this situation, the recommendation is the treatment of the neck with classic or modified radical dissection associated with elective parotidectomy in primaries of anterior regions of scalp and lateral face (Barzilai, Greenberg et al 2005;Jennings and Schmults 2010). Fig.…”
Section: Treatment Of Regional Metastasismentioning
confidence: 99%